PENGARUH LATIHAN DODGE BALL TERHADAP KETERAMPILAN MENGGIRING BOLA PADA PEMAIN SEPAKBOLA SSB RUMBAI PRATAMA - Yovi Tri Rizki Tri Rizki; Ramadi Ramadi '; Ardiah Juita Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was conducted to determine whether there are effects of exercise Dodge ball against the skills of dribble on the football players SSB Rumbai Pratama. This research is a form of research with experimental (Experimental), with a population of athletes football club SSB Rumbai Pratama, in this study all the data population 18 people. The instrument used in this study is to test the dribble, which aims to measure dribble skills with foot speed in changing direction. Afterthat, the data is processed with statistics, with test normality test at a significant level 0,05α lilifors. Hypothesis, there are significant effects of exercise Dodge ball against the skills of dribble on the football players SSB Rumbai Pratama.Based on T test analysis produced Tcount 1,915 and Ttable 1,740, meaning that Tcount > Ttable , data from pree test football dribble test produced Lcount 0,193 and Ltable 0,200 meaning that Lcount< Ltable, the data is normal, and data from post test football dribble test produced Lcount 0,191 and Ltable 0,200 meaning that Lcount< Ltable, the data is normal. then there are effects of exercise Dodge ball against the skills of dribble on the football players SSB Rumbai Pratama.Keywords: effects exercise Dodge Ball against the skills dribble